2012
DOI: 10.1007/s00449-012-0681-9
|View full text |Cite|
|
Sign up to set email alerts
|

Use of focussed beam reflectance measurement (FBRM) for monitoring changes in biomass concentration

Abstract: The potential of focussed beam reflectance measurement (FBRM) as a tool to monitor changes in biomass concentration was investigated in a number of biological systems. The measurement technique was applied to two morphologically dissimilar plant cell suspension cultures, Morinda citrifolia and Centaurea calcitrapa, to a filamentous bacteria, Streptomyces natalensis, to high density cultures of Escherichia coli and to a murine Sp2/0 hybridoma suspension cell line, 3-2.19. In all cases, the biomass concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…After preparing the paste in the high shear mixer, a portion of the paste was transferred to the FBRM beaker. To minimize the effect of sedimentation on the data, the paste was agitated with the impeller, and the probe was inserted into the sample face to the direction of flow at a downwards angle [12]. Three different agitating speeds (150, 300, and rpm) were used to examine how the agitation speed affected fresh state microstructural behavior and agglomeration strength among the particles.…”
Section: Fresh State Particle Size Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…After preparing the paste in the high shear mixer, a portion of the paste was transferred to the FBRM beaker. To minimize the effect of sedimentation on the data, the paste was agitated with the impeller, and the probe was inserted into the sample face to the direction of flow at a downwards angle [12]. Three different agitating speeds (150, 300, and rpm) were used to examine how the agitation speed affected fresh state microstructural behavior and agglomeration strength among the particles.…”
Section: Fresh State Particle Size Measurementsmentioning
confidence: 99%
“…The aim of this paper is to examine the influence of high shear mixing on the rheological properties and fresh state microstructure of Portland cement pastes. The fresh state microstructure was assessed with a focused beam reflectance measurement (FBRM) [12][13][14] device. The results obtained are then discussed on the basis of hydration kinetics and a shear-based agglomeration model, and a mechanism is proposed to explain the effect of high shear mixing on the rheological behavior and microstructural development of the pastes.…”
Section: Introductionmentioning
confidence: 99%
“…The Focused Beam Reflectance Measurement (FBRM) is a well-established method which has found extensive usage in online and in situ particle characterisation within the pharmaceutical and fine chemicals (Kougoulos et al, 2005;Nagy et al, 2008;Saleemi et al, 2012), food (Haddad Amamou et al, 2010;Arellano et al, 2012;Ndoye et al, 2013;Ndoye and Alvarez, 2015) and biotechnology industries (McDonald et al, 2001;Pearson et al, 2003;Jeffers et al, 2003;Whelan et al, 2012). This technique operates on the principle of laser backscattering wherein a laser beam scans in a circular path at a fixed speed through a probe immersed in the solution under study.…”
mentioning
confidence: 99%
“…It should be noted however that the measured droplet size distribution does not depend on the magnitude of the difference in reflectance between the dispersed and continuous phases so long as the difference is sufficient to distinguish the two phases as in our systems. A large community of users have successfully applied FBRM technology for monitoring dynamic solid-liquid or gasliquid processes, such as particle flocculation (Thapa et al, 2009;Kirwan, 2009;Owen et al, 2007), ice and hydrate formation (Greaves et al, 2008), crystal growth under antisolvent addition or cooling (Hermanto et al, 2012;Li et al, 2013Li et al, , 2014Zhao et al, 2012), biomass concentration in a number of biological systems (Whelan et al, 2012), etc. FBRM has also been applied to liquidliquid emulsion systems (Dowding et al, 2001;Maass et al, 2011), and previous results already showed FBRM to be a very practical tool in studying emulsion stability (Cobbledick et al, 2014).…”
Section: Introductionmentioning
confidence: 99%